Looking ahead: Lifestyle advice and disease prevention in community practice. Issue 11 (November 2020) - Cartwright, David
Abstract : With many of the risk factors for eye disease, and poor health in general, being modifiable, David Cartwright explains why eye care professionals are well placed to introduce tailored advice about lifestyle change, and shows how local schemes are already contributing to improvements in long term health profiles. The previous focus on treatment and correction is currently under severe strain and a structured approach to improved prevention is likely to be an important part of our role in years to come (C76817, one distance learning CET point suitable for optometrists and dispensing opticians)